Effect of ZnO nanomaterials coated glass growth duration to the adjacent microfiber light transmission at room temperature - Jali, Mohd Hafiz; Abdul Rahim, Hazli Rafis; Md Johari, Md Ashadi; Mohd Yusof, Haziezol Helmi; Johari, Siti Halma; Ahmad, Aminah (Optical Society of Malaysia (OSM), 2021)
This paper reported the effect of ZnO nanorods growth time to the light transmission of the silica optical fiber. It was conducted by placing silica microfiber on a glass surface coated with Zinc Oxide (ZnO) nanorods. The microfiber was initially tapered into waist diameters of 10 μm using flame brushing technique. Then, the glass substrates were coated with ZnO nanorods for 6 hours, 9 hours, 12 hours, 15 hours, 18 hours and 21 hours of growth time using hydrothermal synthesis technique. Amplified Spontaneous Emission was launched at one end of the microfiber and the other end was connected to the Optical Power Meter to observe the output light transmission behaviour. The samples were tested at room temperature to observe several performance items such as transmitted power, transmission loss and scattering coefficient. Based on the experimental results, it was found that 15-hours growth sample produce the best results as compared to the results as compared to the other growth time samples in term of transmitted power, transmission loss and normalize scattering coefficient. The behaviour of the light transmission changes in different growth time samples. This work could be benefitted in design consideration for various sensing application at room temperature.